Evidence of distinct phase transformations in lithium phosphate glass Li2O-P2O5 - Yukimitu, K.; Araujo, E. B.; Moraes, João Carlos Silos [UNESP]; Reynoso, VCS; Carvalho, C. L. (Iop Publishing Ltd, 2002)
The purpose of this work is to study the Li2O-P2O5 glass using the differential scanning calorimetry (DSC) and x-ray diffraction (XRD) techniques to understand the crystallization process in this glass matrix. To study the glass by DSC, screened samples with different particle sizes to resolve the crystallization peaks were used. Both crystallization peaks were attributed to Li6P6O18 and LiPO3 phases. This evidence was corroborated by XRD analysis on glasses annealed at different temperatures in order to crystallize these phases.